Answer:
x = ± 1, x = ± 2
![√(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/s33jigmx2gpnx3clkmjv4r9kg3iye7ic35.png)
Explanation:
Given
- 13x² + 12 = 0
Use the substitution u = x² , then
u² - 13u + 12 = 0 ← in standard form
(u - 1)(u - 12) = 0 ← in factored form
Equate each factor to zero and solve for u
u - 1 = 0 ⇒ u = 1
u - 12 = 0 ⇒ u = 12
Now substitute x² = u back, that is
x² = 1 ( take the square root of both sides )
x = ±
= ± 1
x² = 12 , then
x = ±
= ±
= ± 2
![√(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/s33jigmx2gpnx3clkmjv4r9kg3iye7ic35.png)